HUBUNGAN FAKTOR LINGKUNGAN RUMAH DENGAN KEJADIAN TB PARU DI KOTA MAGELANG - Erlin Fitria Dewi; Suhartono Suhartono; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2015)
In Magelang, the source infection of TB is still high. Previous research about TB in association with environmental risk factors showed controvercial results. The objective of this study is to analyze the association between environmental house factors with TB incidence in Magelang. A case control design with observational analytic method was applied for this study with a total of 120 respondents matched using purposive sampling. Chi square statistic and multivariate tests were applied for data analysis with significance level of p≤0,05 and 95% confidence interval.Multivariate analysis showed the type of wall OR=3,819 (95%CI=1,467-9,884,p=0,006), the floor type OR=4,034 (95%CI=1,217-13,367,p=0,022), the humidity level OR=2,846 (95%CI=1,124-7,204,p=0,027), the source of infection OR=2,890 (95%CI=0,872-9,580,p=0,083). It can be concluded that there is an association between wall substance, temperature and humidity with TB cases in Magelang. It is expected that the window function to be optimized so that the air circulation from outside to inside of the house can occur.